Different inflow control methods in cirrhotic patients undergoing laparoscopic liver resection - Wang, Zhong Kai; Koh, Ye Xin; Chan, Chung Yip; Lee, Ser Yee (Laparoscopic Surgery, 2019)
In the last decade, laparoscopic liver resection (LLR) has been adopted increasingly worldwide (1,2). This observed trend is promising despite the initial significant learning curve required for LLR (3-5). Even with today’s technological advances such as high definition 3-dimension visualization, improved energy devices and ultrasonic dissectors, hepatobiliary surgeons are still faced with challenges when performing liver resection on cirrhotic livers. This is because cirrhotic patients require not only extensive pre-operative planning and optimization, but also challenging post-operative care (6,7). Intra-operatively, the mobilization and transection of a hard-nodular cirrhotic liver is arduous and regardless of the technique employed, intra-operative vascular control is critical due to the direct impact intra-operative blood loss has on post-operative recovery and long-term oncological outcomes (8).